Compression Behavior of Confined Columns with High-Volume Fly Ash Concrete - Sung-Won Yoo; Young Cheol Choi; Wonchang Choi (Advances in Materials Science and Engineering)
The use of fly ash in ordinary concrete provides practical benefits to concrete structures, such as a gain in long-term strength, reduced hydration heat, improved resistance to chloride, and enhanced workability. However, few studies with high-volume fly ash (HVFA) concrete have been conducted that focus on the structural applications such as a column. Thus, there is a need to promote field applications of HVFA concrete as a sustainable construction material. To this end, this study investigated the compressive behavior of reinforced concrete columns that contain HVFA with a 50 percent replacement rate. Six columns were fabricated for this study. The study variables were the HVFA replacement rate, tied steel ratio, and tie steel spacing. The computed ultimate strength by the American Concrete Institute (ACI) code conservatively predicted the measured values, and, thus, the existing equation in the ACI code is feasible for confined RC columns that contain HVFA. In addition, an analysis model was calibrated based on the experimental results and is recommended for predicting the stress-strain relationship of confined reinforced concrete columns that contain HVFA.